1975
DOI: 10.1021/ac60353a009
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nitrate in water with an ammonia probe

Abstract: This article describes manual and automatic procedures for the determination of nitrates In water containing ammonia by means of an ammonia probe. The nitrates are determined by measuring the ammonia produced during a heterogeneous reduction by means of Devarda alloy powder. The yield of the nitrate reduction with the Devarda alloy was quantitative. The method shows good accuracy and reproducibility and can be applied in waters ranging from mineral water to sewage. Procedures for the elimination of excess ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…After the gas sample was taken, a portion of the remaining soil was extracted with 2 N KCI for NHa+-N determination with an ammonia electrode (Mertens et al 1975). The other portion was extracted with water to determine the NOI-N and NO;-N using an autoanalyzer by the method of Kamphake et al (1967).…”
mentioning
confidence: 99%
“…After the gas sample was taken, a portion of the remaining soil was extracted with 2 N KCI for NHa+-N determination with an ammonia electrode (Mertens et al 1975). The other portion was extracted with water to determine the NOI-N and NO;-N using an autoanalyzer by the method of Kamphake et al (1967).…”
mentioning
confidence: 99%
“…Previous investigators (Mertens et al, 1975) found that it was necessary to form plastic bonded Devarda alloy beads since the available powder was not conducive to the high flow rates utilized with the automated electrode detector system. We had no problem in obtaining the commercial alloys in the 50 mesh or loss variety.…”
Section: Performance Of Reduction Columnmentioning
confidence: 99%
“…1 Thanks to the great advances made in data science, nanotechnology, and measurement techniques in the past years, innovations have also occurred in sensor technologies. These innovations have enabled us to develop new though measuring the levels of ammonium and nitrate ions via several well-established methods such as UV-Vis spectrophotometry or colorimetry 16 can provide valuable information, all of these methods have some difficulties such as needing laboratory conditions, frequent sampling, and transportation of samples. A well-implemented wireless sensing system involving nitrate and ammonium sensors can help mitigate such problems by continuous acquisition and transfer of necessary water quality data.…”
Section: Introductionmentioning
confidence: 99%